Avaliação dos efeitos da estimulação cerebral profunda no núcleo anterior do tálamo sobre a aprendizagem espacial em ratos epilépticos - Ferreira, Elenn Soares [UNIFESP] (2016)
Introduction: Cognitive impairment is a significant comorbidity of temporal lobe epilepsy (TLE) and has been extensively examined in rodent models. Memory deficits may occur soon after status epilepticus (SE), an event associated with extensive cell loss in temporal lobe structures, including the hippocampus. Deep brain stimulation (DBS) of anterior thalamus nucleus (AN) has been used in clinical and preclinical studies as alternative treatment for focal epilepsies. In addition to an anticonvulsant effect, AN DBS delivered during status has been recently shown to have a neuroprotective effects, reducing SE-induced hippocampal inflammatory changes and apoptosis. Objective: Bearing this in mind, we hypothesized that AN DBS administered during SE and the silent phase of pilocarpine TLE model would reduce the cognitive impairment observed in this model. Material and methods: To test this hypothesis, rats that developed pilocarpine-induced SE were given either AN DBS during 6h following the onset of seizures. In a second batch of rats, stimulation treatment continued during the silent phase of the model. Four months following pilocarpine injections, all groups underwent water maze testing and subsequent histological evaluation. Results: DBS-treated animals had longer latency to SE onset (p<0.001). Animals stimulated only during status (EpiDBSa group) or also latent phase (EpiDBSi group) had similar latency to the first spontaneous seizure when compared with non-implanted animals (pilocarpine control, Epi group; p = 0.46). All groups learned the spatial task but with significant, but similar deficit observed among all epileptic groups. AN DBS resulted in neuroprotection of hippocampal cells in CA1 and dentate gyrus. No differences were detected in the mossy fiber sprouting among stimulated and non-stimulated epileptic rats. Conclusion: Our data suggest that AN DBS has neuroprotective role on hippocampal cells but this was not enough to prevent the cognitive decline in pilocarpine-treated chronic epileptic rats.